Assessing inflammatory liver injury in an acute CCl4 model using dynamic 3D metabolic imaging of hyperpolarized [1‐13C]pyruvate. (16th October 2015) - Josan, Sonal; Billingsley, Kelvin; Orduna, Juan; Park, Jae Mo; Luong, Richard; Yu, Liqing; Hurd, Ralph; Pfefferbaum, Adolf; Spielman, Daniel; Mayer, Dirk
Abstract : To facilitate diagnosis and staging of liver disease, sensitive and non‐invasive methods for the measurement of liver metabolism are needed. This study used hyperpolarized 13 C‐pyruvate to assess metabolic parameters in a CCl4 model of liver damage in rats. Dynamic 3D 13 C chemical shift imaging data from a volume covering kidney and liver were acquired from 8 control and 10 CCl4 ‐treated rats. At 12 time points at 5 s temporal resolution, we quantified the signal intensities and established time courses for pyruvate, alanine, and lactate. These measurements were compared with standard liver histology and an alanine transaminase (ALT) enzyme assay using liver tissue from the same animals. All CCl4 ‐treated but none of the control animals showed histological liver damage and elevated ALT enzyme levels. In agreement with these results, metabolic imaging revealed an increased alanine/pyruvate ratio in liver of CCl4 ‐treated rats, which is indicative of elevated ALT activity. Similarly, lactate/pyruvate ratios were higher in CCl4 ‐treated compared with control animals, demonstrating the presence of inflammation. No significant differences in metabolite ratios were observed in kidney or vasculature. Thus this work shows that metabolic imaging using 13 C‐pyruvate can be a successful tool to non‐invasively assess liver damage in vivo . Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Metabolic imaging using 13 C‐pyruvate was used to non‐invasively assess liver damage in vivo, and revealed increased conversion of pyruvate to alanine (rAUCPA ) in livers of CCl4 ‐treated rats, which is indicative of elevated ALT activity as seen in the ALT assay. Conversion of pyruvate to lactate (rAUCPL ) was also higher in CCl4 ‐treated compared with control animals, demonstrating the presence of inflammation, matching the liver injury seen by liver histology.